Thermal efficiency enhancement of thermoelectric module system for cold-hot water dispenser; Phase II. (November 2019) - Wiriyasart, S.; Hommalee, C.; Prurapark, R.; Srichat, A.; Naphon, P.
Abstract: The thermal efficiency enhancement of thermoelectric module system for cold-hot water dispenser has been continuously performed. In the present study, the water block embedded with heat sink has been designed and simulated to obtain the maximum cooling capacity which five and three thermoelectric plates are used for the cold and hot water modules, respectively. The cooling-heating capacity and energy consumption of the cold-hot water dispenser with thermoelectric module system (TMS II) are compared with those from the conventional cold-hot water dispenser with compression refrigeration system (CRS) and those from the prototype of the cold-hot water dispenser with thermoelectric module system (TMS I) from prior works. It found that the lowest and the highest temperatures of cold and hot water from TMS II are 8 °C, 64 °C, respectively, which in the using range temperature of prior cold-hot water dispenser. The energy consumption of TMS II is 29.31% lower than that of the prototype (TMS I) and the same level with CRS. The obtained results are expected to guideline that will allow designing the cold-hot water dispenser with thermoelectric module system.